Market discipline and the Russian interbank market - Irina Andrievskaya; Maria Semenova (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
The interbank market plays an important role in the overall function of the financial system. The efficiency of the interbank market, in turn, depends largely on its inherent disciplining mechanisms. This paper investigates the discipline mechanisms of Russia's interbank market, testing the hypothesis that market discipline in Russia was strong enough to constrain excessive risk-taking by participating banks before, during, and after the 2008- 2009 financial crisis. The existence of quantity-based market discipline is investigated using Heckman's sample selection model and the efficiency of market discipline is studied with a panel data model. Our approach detects market discipline only during the financial crisis, not before or after. Even during the crisis, its efficiency in curbing bank risk-taking was rather low.
URN:NBN:fi:bof-201408072110
Keywords: G21; G01; 330; market discipline; interbank market; risk-taking; banks; Russia